Rigor and differentiation in the classroom tools and strategies - Blackburn, Barbara R. 1961- (New York Routledge, 2019)
"Learn how to differentiate instruction while maintaining a rigorous learning environment. In this practical book, rigor expert Barbara R. Blackburn shows that the differentiated classroom doesn't mean extra work for top students and easy work for others; instead, you can have high expectations for all students and provide scaffolding so that everyone can reach success. She also addresses many of the greatest concerns teachers have about implementing differentiated instruction, including: How to manage your time so that you can create lessons, find resources, and grade assignments for students working at different levels; How to balance differentiated instruction and teaching standards; How to ensure rigor at all tiers of instruction; how to collaborate with teachers and other faculty members;How to differentiate homework and other out-of-class assignments; How to explain differentiated instruction to parents and families; And more... Each chapter includes practical tools and activities that you can use immediately to bring all students to higher levels of achievement."--Provided by publisher.
Introduction --Rigor and differentiation -- Learning portraits -- Expectations -- Differentiating instructional support to increase rigor -- Differentiating a rigorous demonstration of learning -- Managing the rigorous, differentiated classroom -- Common concerns -- Leading change for rigor in the differentiated classroom.
Includes bibliographical references (pages 211-214)
Keywords: Teachers -- Time management; Education -- Study and teaching; Individualized instruction; Teacher-student relationships